2021
DOI: 10.17129/botsci.2715
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacology of the Asteraceae family in Mexico

Abstract: Background: In Mexico, the Asteraceae are part of traditional knowledge where its members have several uses, but they are particularly remarkable in traditional medicine and are used for different purposes. Questions: What pharmacologically studies have been carried out with Asteraceae species used in Mexican traditional medicine? What pharmacological activities have been tested? What compounds are responsible for the tested activities? Species studied: Asteraceae species used in Mexican traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 235 publications
0
2
0
1
Order By: Relevance
“…Gymnosperma glutinosum fue la segunda planta con mayor número de polinizadores. En México se considera una planta medicinal y terapéutica importante (Cilia-López et al 2021). En la literatura no se encontraron registros sobre su asociación con polinizadores, por lo que M. zapoteca , Augochlorella sp ., Pemphredoninae sp.…”
Section: Resultados Y Discusiónunclassified
“…Gymnosperma glutinosum fue la segunda planta con mayor número de polinizadores. En México se considera una planta medicinal y terapéutica importante (Cilia-López et al 2021). En la literatura no se encontraron registros sobre su asociación con polinizadores, por lo que M. zapoteca , Augochlorella sp ., Pemphredoninae sp.…”
Section: Resultados Y Discusiónunclassified
“…Many members of this family are widely studied for their bioactive chemical constituents such as chlorogenic acid, sesquiterpene lactones, benzofurans, diterpenes, flavonoids, pentacyclic triterpene alcohols, terpenoid essential oils, ligand, polyphenols, alkaloids, fatty acids, phenolic acids, tannins, iridoids and polyacetylenes (Heywood et al 1977a,b, Calabria et al 2009, Yaoita et al 2012, Konovalov 2014, Benítez et al 2021, Rolnik & Olas 2021. Pharmacological studies showed that some species exhibit potent anticancer, antioxidant, antibacterial, anti-fungal, anti-inflammatory, antiproliferative, wound-healing, antihemorrhagic, antipyretic, diuretic, hepatoprotective, anti-tussive, antiparasitic, insecticidal and antispasmodic activities, among others (Koc et al, 2015, Carvalho et al 2018Panda & Luyten 2018, Cilia-López et al 2021, Rolnik & Olas 2021. Therefore, extensive phytochemical and pharmacological evaluations of some of the utilized Asteraceae species can lead to discovery and development of novel pharmaceutical products, functional food ingredients and cosmetic products.…”
Section: Introductionmentioning
confidence: 99%
“…Strother (= Dyssodia appendiculata Lag.) is used in Oaxaca, Mexico to treat candidiasis and pain (head, stomach, and gums) and has antibacterial activity ( Frei et al, 1998 ; Cilia-López et al, 2021 ). A. aurantium (L.) Strother is used as an infusion to treat intestinal diseases (amoebiasis).…”
Section: Introductionmentioning
confidence: 99%